2017
DOI: 10.1177/0091552117743567
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Their Family Capital: How Latino Males Successfully Navigate the Community College

Abstract: The purpose of this study is to apply Yosso's community cultural wealth framework to the experiences of Latino male community college students to understand how they balance family obligations, work, and academics while also navigating their educational pathways. Method: The research team conducted 23 semistructured focus groups with 130 Latino male students enrolled full-and part-time at seven distinct community colleges in Texas. Results: Findings reveal the important role family members play in the educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 31 publications
1
48
1
Order By: Relevance
“…In this current article, while we argue that the HBCU environment and as well as faculty, staff, and administrators imbue students with CCW in the form of aspirational, linguistic, navigational, familial, and resistant capital, others have discussed how family and mentors of Latinx students provide them with a sense of familial, aspirational, and navigational capital, which have helped to promote and sustain their academic achievement (Espino, 2014, 2016; Huber, 2009; Larrotta & Yamamura, 2011; Luna & Martinez, 2013; Saenz, Garcia-Louis, Drake, & Guida, 2018). Specifically, in qualitative study with 130 of Latinx male students enrolled across several community colleges, Saenz et al (2018) explained that the family of the participants not only provided them with familial capital, but also from their family networks, they were provided with aspirational capital. Similarly, the participants in Saenz et al’s (2018) study explained that they found navigational capital through their mentors in college, given that many of the participants’ parents lacked a college education.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this current article, while we argue that the HBCU environment and as well as faculty, staff, and administrators imbue students with CCW in the form of aspirational, linguistic, navigational, familial, and resistant capital, others have discussed how family and mentors of Latinx students provide them with a sense of familial, aspirational, and navigational capital, which have helped to promote and sustain their academic achievement (Espino, 2014, 2016; Huber, 2009; Larrotta & Yamamura, 2011; Luna & Martinez, 2013; Saenz, Garcia-Louis, Drake, & Guida, 2018). Specifically, in qualitative study with 130 of Latinx male students enrolled across several community colleges, Saenz et al (2018) explained that the family of the participants not only provided them with familial capital, but also from their family networks, they were provided with aspirational capital. Similarly, the participants in Saenz et al’s (2018) study explained that they found navigational capital through their mentors in college, given that many of the participants’ parents lacked a college education.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, in qualitative study with 130 of Latinx male students enrolled across several community colleges, Saenz et al (2018) explained that the family of the participants not only provided them with familial capital, but also from their family networks, they were provided with aspirational capital. Similarly, the participants in Saenz et al’s (2018) study explained that they found navigational capital through their mentors in college, given that many of the participants’ parents lacked a college education. In all, the way we discussed how HBCU students have gained various tenets of CCW from the HBCU milieu is similar to how Latinx students have gained similar variations of CCW from their families and others (i.e., mentors).…”
Section: Discussionmentioning
confidence: 99%
“…The latter, although a positive influence, also caused tension between students’ commitment to their education and responsibility to family. As noted by Sáenz, García‐Louis, Drake, and Guida (), familismo plays a meaningful role in the way Latino men interpret and navigate their college experience. On one hand, earning a college degree inspired a sense of pride, not only for Latino men, but also for the entire family.…”
Section: The Role Of Family For Latino Men In Community Collegementioning
confidence: 96%
“…A consistent finding across studies is the negative impact lack of financial means has on Latino males' academic and extracurricular engagement. Latino males report feeling increased pressure to work while in college to help sustain their family, but they took pride in helping (Sáenz, García-Louis, Drake, & Guida, 2018). Crisp and Nora (2010) identified environmental pull factors that draw Latina/o students' attention away from academics to external factors of university life such as working, commuting, parttime status, and other financial obligations.…”
Section: Latino Males In Higher Educationmentioning
confidence: 99%
“…In fact, Latina/os, as a whole, are significantly less likely than other groups to accept educational loans and accumulate student debt (Krogstad, 2016). Therefore, many Latino males find themselves working multiple jobs while enrolled in college (Sáenz et al, 2018), they tend to enroll in community colleges at higher rates than any other group (Krogstad), and they enroll part-time rather than full-time (Sáenz & Ponjuán, 2011). The noted factors are not unique to Latino males, but extant literature accentuated that these common threads can manifest into unfavorable circumstances which can inhibit (or slow down) their academic persistence.…”
Section: Latino Males In Higher Educationmentioning
confidence: 99%